Angiogenesis and lymphangiogenesis in stage 1 germ cell tumours of the testis. - Jones, A; Fujiyama, C; Turner, K; Fuggle, S; Cranston, D; Turley, H; Valtola, R; Bicknell, R; Harris, A (2000)
OBJECTIVE: To determine whether angiogenesis can be used as an additional prognostic indicator in patients with stage 1 germ cell tumours of the testis. PATIENTS AND METHODS: Paraffin sections were assessed immunohistochemically from 51 patients with clinical stage 1 germ cell tumours of the testis (28 seminoma, 23 teratoma) treated by orchidectomy and surveillance only. Sections were analysed for microvascular density (MVD), and expression of the angiogenic factors vascular endothelial growth factor (VEGF) and thymidine phosphorylase (TP). In addition, in the seminoma cases the presence of mRNA for the lymphangiogenic factor VEGF-C was examined by in situ hybridization, and its corresponding receptor VEGFR-3 by immunohistochemistry. RESULTS: Teratoma specimens had a significantly higher mean (range) MVD (85, 26-163; P < 0.01) than both seminoma (37, 16-91) and four normal specimens (26, 18-30). Teratoma specimens also had significantly higher VEGF expression than both seminoma and normal specimens (P < 0.01). Despite these differences between groups, and indeed individual tumours, there was no significant correlation between MVD and VEGF, or between either MVD or VEGF and relapse-free survival. TP expression was significantly greater in tumours than in normal specimens (P < 0.02) but with very little inter-tumour variation. VEGF-C mRNA and VEGFR-3 protein were detected in a third to a half of cases, with expression mostly around endothelial vessels. CONCLUSIONS: The marked differences between normal testis and tumours implicate angiogenesis in the biology of germ cell tumours of the testis. In addition, the detection of factors involved in lymphangiogenesis in some seminomas, tumours which initially metastasize primarily to lymph nodes, indicate that although not prognostic in this study, further studies are warranted in both these areas in the search for further prognostic indicators and therapeutic targets.